2012
DOI: 10.1074/jbc.m112.346296
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Induces Vascular Endocannabinoid Release, Which Attenuates Its Vasoconstrictor Effect via CB1 Cannabinoid Receptors

Abstract: Background:In expression systems diacylglycerol (DAG) produced during AT 1 angiotensin receptor signaling can be converted to 2-arachidonoylglycerol. Results: Inhibition of CB 1 receptors and DAG lipase augmented angiotensin II-induced vasoconstriction in resistance arteries. Conclusion: Angiotensin II-induced vasoconstriction is attenuated via 2-arachidonoylglycerol release and consequent CB 1 receptor activation. Significance: This is the first demonstration that angiotensin II-induced endocannabinoid releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…8). Similar to the present findings, activation of Agtr1 induced CB 1 Rmediated effects in other tissues via increasing the synthesis of the endocannabinoid 2-arachidonoyl glycerol (49,50), whereas CB 1 R blockade was found to down-regulate AGT1R (51). There is also evidence that CB 1 R involvement in angiotensin IIinduced pathologies may reflect Agtr1/CB 1 R heteromerization, a process which amplifies Agtr1 signaling (52).…”
Section: Discussionsupporting
confidence: 89%
“…8). Similar to the present findings, activation of Agtr1 induced CB 1 Rmediated effects in other tissues via increasing the synthesis of the endocannabinoid 2-arachidonoyl glycerol (49,50), whereas CB 1 R blockade was found to down-regulate AGT1R (51). There is also evidence that CB 1 R involvement in angiotensin IIinduced pathologies may reflect Agtr1/CB 1 R heteromerization, a process which amplifies Agtr1 signaling (52).…”
Section: Discussionsupporting
confidence: 89%
“…The receptor plays role in many important physiological processes, such as learning, thinking, nociception or the regulation of food-intake (Pacher et al, 2006). Activation of presynaptic CB 1 Rs by postsynaptic endocannabinoid release, which mediates retrograde transmission, is a key regulatory mechanism in the central nervous system, but paracrine activation of CB 1 Rs with a similar mechanism can also occur in extraneural tissues (Freund et al, 2003;Gyombolai et al, 2012;Sanchez et al, 2001;Turu et al, 2009;Szekeres et al, 2012). The cellular signaling events following CB 1 R activation are mainly associated with the activation of heterotrimeric G i/o -proteins and include inhibition of adenylyl cyclases, activation of K ir channels, inhibition of Ca v channels and phosphorylation and activation of different subtypes of mitogen-activated protein kinases (MAP kinases) (Turu and Hunyady, 2010).…”
mentioning
confidence: 99%
“…Er-Ning Su et al also highlighted the critical role of the endothelium in cannabinoid-induced vasoactivity in isolated perfused retinal arterioles [15]. However, other studies have suggested that R-(+)-WIN55212-2-induced relaxation is endothelium independent in other vessels, including the rat small mesenteric artery [43] and gracilis arterioles [21]. Interestingly, using the bovine ophthalmic artery, Romano et al demonstrated that both endothelium-dependent and -independent pathways are involved in cannabinoid-agonist-induced relaxation [17].…”
Section: Discussionmentioning
confidence: 99%